OPTIMALISASI FUNGSI INTELIJEN KEPOLISIAN DALAM PENYELIDIKAN TINDAK PINDANA NARKOTIKA YANG DILAKUKAN ANGGOTA KEPOLISIAN ( Studi Sat Intelkam Polres Solok) - Harefa, Herius (LPPM Universitas Ekasakti Padang, 2018)
One of the tasks of intelligence is to investigate members of the Police who commit criminal acts of narcotics abuse. Based on this, the problems described are the first, how the Police Intelligence Function and constraints in the Investigation of Narcotics Crimes committed by Solok Police Force Members and the Optimization of the Intelligence Functions. The specifications of this study are analytical descriptive. While the method of approach used is juridical empiris.Teknik data collection is a field study through interviews for primary data and literature study to obtain secondary data. The data obtained are then analyzed qualitatively. The first conclusion of the Police Intelligence Function in the investigation and supervision of members of the Police who committed the narcotic crime is to search, dig, and collect data as completely as possible from various sources. Both obstacles encountered in the execution of these functions are law enforcement factors where the Police must crack down on its members who commit a crime not to protect its members who are involved in narcotic criminal acts. Efforts Optimizing the intelligence function in investigating drug abuse by members of Polri is Conducting Education and training for members of Intelligence, Coordinating and cooperation with related institutions and institutions. Repressive efforts as law enforcement efforts in the form of repression, eradication, crackdown after the crime occurred.